2019
DOI: 10.2147/ott.s208133
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA LINC01116 Promotes Cancer Cell Proliferation, Migration And Invasion In Gastric Cancer By Positively Interacting With lncRNA CASC11</p>

Abstract: PurposeThe oncogenic roles of lncRNA LINC01116 have been reported in several types of cancer, while its involvement in gastric cancer is unknown. This study aimed to investigate the involvement of LINC01116 in gastric cancer.MethodsGene expression was detected by qPCR. Correlations were analyzed by linear regression. Overexpression and siRNA silencing techniques were used to analyze gene functions. Cell invasion and migration were analyzed by Transwell assays.ResultsLINC01116 and lncRNA CASC11 were both upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…LncRNA LINC01116 has been shown to play an oncogenic role in multiple human cancers. [17][18][19][20][21] qPCR assay detected up-regulation of LINC01116 expression in prostate cancer cells as compared to that in normal human prostate epithelial cells, which encouraged the subsequent functional assays. 16 siRNA-induced knockdown of LINC01116 decreased prostate cancer cell proliferation, and the disruption of the LINC01116 gene with a CRISPR/CAS9 system resulted in a four-fold reduction in the number of prostate cancer cell colony formation, which supporting the oncogenic role of LINC01116 in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LncRNA LINC01116 has been shown to play an oncogenic role in multiple human cancers. [17][18][19][20][21] qPCR assay detected up-regulation of LINC01116 expression in prostate cancer cells as compared to that in normal human prostate epithelial cells, which encouraged the subsequent functional assays. 16 siRNA-induced knockdown of LINC01116 decreased prostate cancer cell proliferation, and the disruption of the LINC01116 gene with a CRISPR/CAS9 system resulted in a four-fold reduction in the number of prostate cancer cell colony formation, which supporting the oncogenic role of LINC01116 in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LINC01116 was reported to overexpressed and contributed to the progression of nasopharyngeal carcinoma, gastric cancer, osteosarcoma, glioma, epithelial ovarian cancer and head and neck squamous cell carcinoma. [17][18][19][20][21][22][23] However, there is little knowledge on the role of LINC01116 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more studies showed that lncRNAs were involved in chromosome regulation, transcription and post-transcriptional regulation [4][5]. It has also been observed to be involved in the development and progression of other cancers, such as gastric cancer and liver cancer [6][7]. Several prognostic biomarkers for LUAD have been reported such as lncRNA LOC100132354 [8]and lncRNA CTB-193M12.5 [9], etc.…”
Section: Introductionmentioning
confidence: 99%